Edukasi Interaktif Pencegahan Perundungan dan Kekerasan Seksual pada Siswa SMA 2 Boyolali: Pengabdian - Abdurrahman Naufal Fakhri; Amalia Julianti; Aditya Verdhi Wibowo; Sri Hartini (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The issue of bullying and sexual violence in schools remains a serious challenge that requires structured educational interventions to create a safe learning space for students. This community service program aims to improve literacy and critical awareness among students at SMAN 2 Boyolali regarding the dangers and psychological impacts of such acts of violence. The program was implemented through an interactive outreach method involving 35 students as active participants. The focus of the material presented included definitions, various forms of physical and non-physical violence, long-term psychological impacts, and safe reporting mechanisms for victims. The program's success was measured through a question-and-answer session after the outreach, which demonstrated an increase in student understanding. As a concrete output, this activity succeeded in forming a group of students within one class who took the initiative to act as proactive anti-violence agents in the school environment. These results conclude that the interactive outreach method is an effective and applicable approach to strengthening student protection in educational units.